Observaciones sobre la ecología del páramo andino de Monserrate Observaciones sobre la ecología del páramo andino de Monserrate - Sturm Helmut; Abouchaar Alberto (Caldasia)
In a paramo region near Bogotá (Colombia), 3.230 m above seal evel investigations were made of clima, soil vegetation and fauna.  The mean temperature was 8.4 degrees C and the annual rainfall 1.221.4 mm. Sometimes great variations of relative humidity and of temperature near the soil surface could be registered. The properties of the black coloured paramo soil, wich probably is not a uniform type, are discussed. Its micromorphology and fauna were examined for the first time. The fauna is well developed and takes part intensivily in mixing the mineral and organic components. The soil type is classified as being between those which KUBIENA (1953) called "Pechtorf" and "Moderranker", The vegetation has been characterized by the estimation of the "Artmächtigkeit" (BRAUN-BLANQUET,1964) of the single species. The distribution and net production of Espeletia grandiflora Humb. & Bonpl., the most specific plant species in this paramo is discussed. The quantitative sampling of the fauna, especially of the arthropod fauna, was carried out by means of a combination of different methods to evaluate the density per litre and the density of activity. The mantle consisting of dead leaves of E. grandiflora proved to be a rich and characteristic "biotope". The facts are discussed partly by comparing them with corresponding facts from a tropical rain forest. In a paramo region near Bogotá (Colombia), 3.230 m above seal evel investigations were made of clima, soil vegetation and fauna.  The mean temperature was 8.4 degrees C and the annual rainfall 1.221.4 mm. Sometimes great variations of relative humidity and of temperature near the soil surface could be registered. The properties of the black coloured paramo soil, wich probably is not a uniform type, are discussed. Its micromorphology and fauna were examined for the first time. The fauna is well developed and takes part intensivily in mixing the mineral and organic components. The soil type is classified as being between those which KUBIENA (1953) called "Pechtorf" and "Moderranker", The vegetation has been characterized by the estimation of the "Artmächtigkeit" (BRAUN-BLANQUET,1964) of the single species. The distribution and net production of Espeletia grandiflora Humb. & Bonpl., the most specific plant species in this paramo is discussed. The quantitative sampling of the fauna, especially of the arthropod fauna, was carried out by means of a combination of different methods to evaluate the density per litre and the density of activity. The mantle consisting of dead leaves of E. grandiflora proved to be a rich and characteristic "biotope". The facts are discussed partly by comparing them with corresponding facts from a tropical rain forest.